MEMBANGUN MORAL MASYARAKAT INDUSTRI: TINJAUAN BUDAYA - Rahmat, Moh. (Jurnal Bestari, 1992)
Culture must not be translated as fashion show or preservation of many historical heritages solely. It includes all aspects of human thought and behaviour. The magnificient trends of technological achievments that spread fastly since the beginning of the last second millenium must be regarded in a close relation with the essence of cultural issues. It is, therefore, important to place the moral and ethics as the fundamental stream colouring men obsession to achieve scientific and technological progress.